Ru (III) Catalyzed Oxidation of Aliphatic Ketones by N-Bromosuccinimide in Aqueous Acetic Acid: A Kinetic Study - P. Giridhar Reddy; K. Ramesh; S. Shylaja; K. C. Rajanna; S. Kandlikar (The Scientific World Journal)
Kinetics of Ru (III) catalyzed oxidation of aliphatic ketones such as acetone, ethyl methyl ketone, diethyl ketone, iso-butylmethyl ketone by N-bromosuccinimide in the presence of Hg(II) acetate have been studied in aqueous acid medium. The order of [N-bromosuccinimide] was found to be zero both in catalyzed as well as uncatalyzed reactions. However, the order of [ketone] changed from unity to a fractional one in the presence of Ru (III). On the basis of kinetic features, the probable mechanisms are discussed and individual rate parameters evaluated.